British foreign policy, national identity, and neoclassical realism - Hadfield, Amelia (The New International Relations of Europe., 2010)
This groundbreaking study offers a genuinely multidisciplinary exploration of cultural influences on foreign policy. Through an innovative blend of historical analysis, neoclassical realist theory, and cultural studies, Amelia Hadfield-Amkhan shows how national identity has been a catalyst for British foreign policy decisions, helping the state to both define and defend itself. Representing key points of crisis, her case studies include the 1882 attempt to construct a tunnel to France, the 1982 Falklands War, and the 2003 decision to remain outside the Eurozone. The author argues that these ev.